STRATEGI KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN (Studi Kasus di Madrasah Aliyah Al-Inayah Depok Kecamatan Pakenjeng Kabupaten Garut) - Hermawati, Tina; Ijudin, Ijudin; Masripah, Masripah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research examines the leadership strategy of the madrasah principal in improving learning effectiveness at Madrasah Aliyah Al-Inayah Depok, Pakenjeng District, Garut Regency. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews with the principal, vice principals, teachers, administrative staff, students, and parents, as well as participatory observation and documentation studies. The findings reveal that the principal's leadership strategy encompasses five dimensions: (1) vision and strategic direction, formulated participatively; (2) multilevel transformational communication through formal meetings, daily WhatsApp motivational messages, and direct classroom visits; (3) responsive and adaptive human resource development through a peer mentoring system and academic supervision with substantive feedback; (4) data-based adaptive innovation, including the Pesantren Kilat program, tightening entry hours, constructing a new gate, and utilizing teachers during vacant class periods; and (5) tiered evaluation and continuous improvement through a three-level PDCA cycle. These strategies synergistically improve the four dimensions of learning effectiveness according to Slavin's QAIT model: quality, appropriate level, incentive, and time. The model is grounded in Islamic Educational Science as grand theory and Islamic Educational Management as middle-range theory, making values-based Islamic leadership the fundamental differentiator of this model.